Exploring Pathways for Addressing Systemic Problems in the Agricultural Sector: The Case of Abamote village, Bosana Worena woreda, Northern Amhara Region, Ethiopia - Dessalegn, Bezaiet; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
The report documents the first steps taken to aims to design a “rapid” systemic approach that can be used to better understand the entry points for systems transformation, and innovation bundling. The tool was tested in three countries including Bangladesh, Nepal and Ethiopia. The report documents the steps taken in the case of Ethiopia.